Surface Design of Liquid Separation Membrane through Graft Polymerization: A State of the Art Review - Deepa Suresh; Pei Sean Goh; Ahmad Fauzi Ismail; Nidal Hilal (Membranes, 2021)
Surface modification of membranes is an effective approach for imparting unique characteristics and additional functionalities to the membranes. Chemical grafting is a commonly used membrane modification technique due to its versatility in tailoring and optimizing the membrane surface with desired functionalities. Various types of polymers can be precisely grafted onto the membrane surface and the operating conditions of grafting can be tailored to further fine-tune the membrane surface properties. This review focuses on the recent strategies in improving the surface design of liquid separation membranes through grafting-from technique, also known as graft polymerization, to improve membrane performance in wastewater treatment and desalination applications. An overview on membrane technology processes such as pressure-driven and osmotically driven membrane processes are first briefly presented. Grafting-from surface chemical modification approaches including chemical initiated, plasma initiated and UV initiated approaches are discussed in terms of their features, advantages and limitations. The innovations in membrane surface modification techniques based on grafting-from techniques are comprehensively reviewed followed by some highlights on the current challenges in this field. It is concluded that grafting-from is a versatile and effective technique to introduce various functional groups to enhance the surface properties and separation performances of liquid separation membranes.